Avaliação da atividade antiproliferativa do extrato hidroalcoólico da própolis vermelha e suas frações obtidas por partição - Lemes, Danieli Cristina (2021)
The present study aimed to evaluate the cytotoxicity of red propolis hydroalcoholic extract (RPHE) and its fractions obtained by partition, hexanes (HF), dichloromethane (DF), ethyl acetate (AF) and n-butanol (BF), on tumor and non-tumor cell lines. For this purpose, the XTT colorimetric assay was performed on human lung fibroblasts (GM07492A, nontumor cell), breast adenocarcinoma (MCF-7), glioblastoma (U343) and cervix adenocarcinoma (HeLa) cells. The results showed that RPHE, HF and DF presented not only cytotoxic potential to all tumor cell lines but also to normal cell line, indicating selectivity absence. HF presented the lowest IC50 (half minimal inhibitory concentration; 33.8-133.3 µg/mL), with significant difference from those observed for RPHE (137.0-262.7 µg/mL). BF and AF revealed an IC50 which was higher than 1250 µg/mL in all cell lines. The results showed that red propolis has substances with antiproliferative activity, indicating that its hexanes fraction may have substances with cytotoxic potential. Key-words: cytotoxicity, red propolis, XTT colorimetric assay